2019
DOI: 10.1159/000501455
|View full text |Cite
|
Sign up to set email alerts
|

Proinsulin-Secreting Neuroendocrine Tumors of the Pancreas: A Single-Centre Experience

Abstract: <b><i>Background:</i></b> Proinsulinoma is a neuroendocrine tumor (NET) of the pancreas that produces prohormone proinsulin. These tumors are very rare. In the literature, they are most often presented in the form of case reports. <b><i>Materials and Methods:</i></b> We studied 177 patients with NET of the pancreas who underwent surgical treatment in the A.V. Vishnevsky National Medical Research Centre of Surgery from January 2007 to December 2018. <b><i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Hypoglycemia due to proinsulinoma is infrequently reported [ 3 , 15 ]. A review of 16 proinsulinoma cases reported a 2:1 female preponderance, with a mean age of diagnosis at 56 years [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoglycemia due to proinsulinoma is infrequently reported [ 3 , 15 ]. A review of 16 proinsulinoma cases reported a 2:1 female preponderance, with a mean age of diagnosis at 56 years [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulated insulin secretion in hyperinsulinemic hypoglycemia (HH) drives glucose into insulin-sensitive tissues (eg, skeletal muscle, adipose tissue, and liver) and further exacerbates insulin-mediated inhibition of glycogenolysis, lipolysis, gluconeogenesis, and ketogenesis, predisposing the individual to hypoglycemic brain injury [ 2 ]. Clinical diagnosis can be challenging since symptoms of hypoglycemia mimic nonspecific symptomatology such as seizures, syncope, or psychiatric illness, resulting in delayed diagnosis for approximately 4 years (range of 1-30 years) [ 1 , 3 , 4 ]. On the other hand, misdiagnosis can lead to unnecessary pancreatotomy [ 4 ].…”
mentioning
confidence: 99%
“…Kringer et al . suggested that a diagnosis of proinsulinoma can be made according to the clinical presentation and an elevated proinsulin level [ 7 ]. In the present case, the patient had hypoglycemic symptoms and a proinsulin level of 408 pmol/l, which is extremely high compared with previous reports of proinsulinoma [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%